Prevalence of Dental Caries and Need of Preventive Dental Materials in the Rawat Community: A Cross-Sectional Public Health Study (2025) - Moin Khan, Meher; Ahmad, Mir Jibran; Qadir, Abdul; Pasha, Mehwish; Bano Lone, Saadia; Haidar, Adeel (Journal of Neonatal Surgery, 2025)
Dental caries is one of the most prevalent oral health problems worldwide, particularly in developing countries like Pakistan where access to oral health care services is limited. The purpose of this study was to determine the prevalence of dental caries among the population of Rawat, Pakistan. A cross-sectional study was conducted at Rawat, Pakistan, over a period of six months (February–July 2025). A total of 400 participants, both males and females aged between 12 and 60 years, were selected through convenience sampling using the WHO sample size calculator version 2.0. Clinical examinations were performed using WHO criteria for the diagnosis of dental caries. Data were entered and analyzed using SPSS version 25.The prevalence of dental caries was found to be 68.5%. Females exhibited a slightly higher prevalence (71.2%) compared to males (65.4%). The highest prevalence was observed among participants aged 21–30 years (75.6%). Socioeconomic status, oral hygiene practices and the lack of an affordable, multifunctional preventive dental hygiene product accessible to populations were significantly associated with the occurrence of caries.These findings highlight the urgent need for preventive oral health programs in semi-urban communities of Pakistan as well as the formulation of a cost-effective, multifunctional agent designed to arrest or reverse early carious lesions. Targeted strategies focusing on oral hygiene education, introduction of preventive dental materials, reduced sugar intake, and improved access to dental care could significantly reduce the disease burden in this population